(untitled) (Global Journal of Science Frontier Research, 2018)
The study conducted to investigate significant anti bacterial activity of egarlic (Alliums sativum L.) peach leave (prunus persica L) and root of ginger (zingiber officinale L) extract to bacteria like salmonella, shigella and E.coli. The objective of the study was to evaluate the antimicrobial activity of fresh botanicals extracts. Fresh botanical plant parts such as leave of prunus persica, root of zingiber officinale L and edible part Alliums sativum L were used for the investigation and fresh parts of plants were crushed by mortar and pestle to extract aqueous. Botanical extract that selected for this study had significantly inhibit for the formation colonies of bacteria spp such as Salmonella typhimurium, Shigella dysentery and Escherichia coli. All Treatments of the present study had showed high toxicity or inhibition of bacteria spp. Colonies when compared with negative treatment. Some aqueous extractions had no significance difference for inhibition of colonies when contrast with positive control (Ampicillin). Among treatments there was high significance difference (p